Criminal Responsibility for Perpetrators of Child Assault (Analysis of Decision Number 2784/Pid.B/2021/Pn Mdn) - Daulay, Puspa Ainni; Sidi, Redyanto; Hasibuan, Aulia Rahman Hakim (Universitas Muhammadiyah Tangerang, 2025)
This paper examines the issue of criminal liability in cases of group assault resulting in child victimization, with reference to Court Decision No. 2784/Pid.B/2021/PN Mdn. Utilizing a normative juridical method and a descriptive approach, the study finds that the criminal act of violence against a child occurred within the context of a youth brawl. The analysis of the court's decision establishes that the defendant committed physical violence causing injury to the child. The court found the defendant guilty of violating Article 80(1) of Law of the Republic of Indonesia No. 35 of 2014, which amends Law No. 23 of 2002 on Child Protection, and sentenced the defendant to imprisonment. The findings underscore the necessity of effective law enforcement in cases of violence against children and call for comprehensive legal protection for child victims.Keywords: criminal liability, group assault, child violence